"In My Own Opinion": Negotiation of Rabbinical Authority Online in Responsa Within Kipa.co.il. (January 2021) - Tsuria, Ruth; Campbell, Heidi A.
Abstract: This study explores how Israeli Jewish rabbis negotiate their authority through the practice of online Responsa, a Jewish tradition of rabbinical questions and answers (Q&A). A total of n  = 567 Q&A were collected from five different rabbis answering on Kipa.co.il. By analyzing questions asked by anonymous users and answered by specific rabbis, this research shows how online Responsa allows rabbis to negotiate their rabbinical authority. We highlight two trends regarding rabbinical authority: (a) a growing need for online presence, meaning that the quantity of answers becomes an important part of constructing rabbinical authority online and (b) online activity in rabbinical Q&A changes the length and textual depth of the answers. The online Jewish Responsa is more concise and tends not to supply textual support. These trends, we argue, result in a reframing of the rabbi's roles, and the Halachic discourse itself.